2014
DOI: 10.1016/j.trsl.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, metabolic dysfunction, and cardiac fibrosis: pathophysiological pathways, molecular mechanisms, and therapeutic opportunities

Abstract: Cardiac fibrosis is strongly associated with obesity and metabolic dysfunction and may contribute to the increased incidence of heart failure, atrial arrhythmias and sudden cardiac death in obese subjects. Our review discusses the evidence linking obesity and myocardial fibrosis in animal models and human patients, focusing on the fundamental pathophysiologic alterations that may trigger fibrogenic signaling, the cellular effectors of fibrosis and the molecular signals that may regulate the fibrotic response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
155
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(173 citation statements)
references
References 131 publications
(156 reference statements)
1
155
0
4
Order By: Relevance
“…Clinical 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 studies demonstrate considerable association between obesity and cardiac fibrosis; potential mechanisms contributing to cardiac fibrosis include hemodynamic factors, neuro-humoral substances, metabolic dysregulation, inflammation and oxidative stress [18,19]. Nevertheless, we previously found that neither metabolic dysfunction (hyperglycemia, insulin resistance and dyslipidemia) nor hypertension was induced in O-MHO pigs [11].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 studies demonstrate considerable association between obesity and cardiac fibrosis; potential mechanisms contributing to cardiac fibrosis include hemodynamic factors, neuro-humoral substances, metabolic dysregulation, inflammation and oxidative stress [18,19]. Nevertheless, we previously found that neither metabolic dysfunction (hyperglycemia, insulin resistance and dyslipidemia) nor hypertension was induced in O-MHO pigs [11].…”
Section: Discussionmentioning
confidence: 99%
“…Diastolic dysfunction is the hallmark of diabetic cardiomyopathy 19,20 and may be due to cardiac hypertrophy, or to the development of interstitial fibrosis 21,22 . Our findings demonstrate that in the db/db mouse model of fibrotic diabetic cardiomyopathy, partial loss of Smad3 improves ventricular compliance (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac fibroblasts play a key role in the pathogenesis of cardiac fibrosis [18]. The epigenetic control of gene expression by the HDAC family has been demonstrated to play critical roles in fibrosis progression and development [19,20].…”
Section: Discussionmentioning
confidence: 99%